Frequency and characteristics of induced abortion among married and single women in São Paulo, Brazil Aborto provocado: sua dimensão e características entre mulheres solteiras e casadas da cidade de São Paulo, Brasil - Rebeca de Souza e Silva; Elisabeth Meloni Vieira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
This article presents the results of a study in the city of São Paulo, Brazil, aimed at estimating the frequency of induced abortion among women 15 to 49 years of age. The objective was to characterize the occurrence of induced abortion by comparing the ideal number of children, age, and contraceptive use between married and single women. Based on random sampling, 1,749 interviews were held, including 764 married women, 658 single women, and 327 with other marital status. The analysis included: mean number of abortions per woman by analysis of variance and proportions of abortions and pregnancy, using the chi-square test. The mean abortion rate for married women (45 per thousand) did not differ statistically from that of single women. However, the pregnancy rate was much lower in single women, and when single women became pregnant they used abortion more frequently; while fewer than 2% of pregnancies in married women ended in induced abortions, among single women the abortion rate exceeded 18%. Therefore, the priority in the reproductive health field should be to invest in the supply and dissemination of appropriate contraceptive methods for women's early sexually active life. Apresenta-se uma pesquisa realizada na cidade de São Paulo, Brasil, para dimensionar o aborto provocado entre mulheres de 15 a 49 anos. O objetivo é caracterizar a ocorrência do aborto provocado analisando o número ideal de filhos, idade e uso de contraceptivos comparando-se as casadas e solteiras. Mediante sorteio aleatório foram realizadas 1.749 entrevistas, sendo 764 com mulheres casadas, 658 com solteiras e 327 de outras categorias maritais. A análise inclui: a média de abortos por mulher, por meio de análise de variância e proporções de aborto e de gestação, usando-se o teste do qui-quadrado. Verificou-se que a média de abortos, 45 por mil, por mulheres casadas não difere da das solteiras. No entanto, as solteiras engravidam numa escala muito menor e, ao engravidarem, recorrem mais largamente ao aborto provocado - enquanto que menos de 2% das gestações das casadas resultam em aborto provocado, entre aquelas esta cifra supera 18%. A prioridade na área de saúde reprodutiva, sem dúvida, deve ser investir na oferta e divulgação de métodos contraceptivos adequados ao início da vida sexual.